Hydatid fluid from Echinococcus granulosus induce the autophagy process in dendritic cells and promote antigen presentation and T- cell proliferation - Chop, Maia (2020)
Background: Autophagy is an important process for the presentation of endogenous and exogenous proteins on MHC I and II molecules, promoting activation of CD8+ and CD4+ T cells respectively. The aim of this work is to analyze if hydatid fluid (HF) from Echinococcus, constituted by a wide range of parasite proteins could trigger autophagy improving antigen presentation and T cell proliferation. Methods: BMDCs were cultured in complete RPMI. Hydatid fluid (HF) was punctured from the hydatid cysts collected of infected cattle slaughtered. Antigen uptake was measured with (FITC-OVA) in BMDCs using a standard method. HF-stimulated BMDCs, were evaluated in autophagy induction and MHC II expression. For it, fixed cells were immunostained with LC3-clone H50 and analyzed them by immunofluorescence confocal microscopy. CFSE-stained splenocytes were co-incubated with BMDCs using a DC: splenocyte ratio of 1:4 Cellular proliferation was assayed after 4 days of culture by flow cytometry. Results: First, we evaluated if stimulation of HF during 18 h in BMDCs, induce different rates of antigen uptake. Effectively, the presence of Echinococcus antigens induces a markedly decreased OVA-uptake compared to control (**p <0.01, n=3). Next, we studied if stimulation with Eg antigens induces changes in the basal level of autophagy. HF-stimulated BMDCs significantly enhanced the mean fluorescence intensity of MHC II and LC3 and showed a trend in the increment of number and the average size of LC3-positive structures in comparison with unstimulated cells (*p<0.05, **p<0.01, ***p<0.001 HF-stimulated cells vs controls). Finally, we observed that culture splenocytes in the presence of stimulated DC induce their proliferation % CFSE+ cells CTRL:99%, HF:55% (***p<0.001, n=3). Conclusions: These data suggest that HF of Echinococcus induces an increase in autophagy processes promoting the presentation of exogenous antigens presented in MHC II molecules to improve T cell proliferation.